DEVELOPING ESL/EFL LEARNERS’ PUBLIC SPEAKING SKILLS THROUGH PECHA KUCHA PRESENTATIONS - Romualdo A. Mabuan (University of Kuningan, 2017)
In the 21st century workplace, there has been an increasing demand for graduates to possess communicative competence particularly in speaking. Anchored on the 21st Century Learning Framework (Partnership for 21st Century Skills or P21, 2006) and the TPACK Framework (Koehler Mishra, 2009), this study reports findings on the pedagogical viability of utilizing Pecha Kucha 20x20 Presentations in developing students’ competence and confidence while presenting in the language classroom. Research participants include 43 English as Second Language (ESL) learners taking Speech Communication classes in a private university in Manila, the Philippines during the second semester of the academic year 2016-2017. Research data from students’ reflections, interviews, survey, and focus group discussion (FGD) suggest that despite some format and technological limitations, delivering Pecha Kucha presentations may help students develop their English speaking and oral presentation skills, build their confidence in speaking before an audience, and practice their English macro skills such as listening and reading. In the light of these findings, pedagogical implications are provided for ESL (English as a second language) and EFL (English as a foreign language) teachers, communication educators, and researchers.Keywords: Teaching speaking, Pecha Kucha Presentations, ESL public speaking, TPACK